IMPLEMENTASI HEALTH BELIEF MODEL DALAM MENGANALISIS SAFETY BEHAVIOR PEKERJA DI UNIT BLASTING DAN PAINTING PT. MCDERMOTT INDONESIA TAHUN 2021 - Fakhira Khairunnisa Binti Ahmad Herzy, Dhea (2022)
Work accidents still often occur in the offshore construction sector, especially in blasting and painting. The hazards and risks involved in blasting and painting can be minimized by practicing good safety behavior at work. This study aims to analyze the relationship of the Health Belief Model to safety behavior in the blasting and painting PT. McDermott Indonesia. This study uses a quantitative method with a cross-sectional. The total population in this study was 100 workers with a total sample of 80 workers. The sampling technique was purposive sampling. Based on the results of the study, it was found that of the 6 dimensions of the Health Belief Model studied, two dimensions have a significant relationship with safety behavior. The two dimensions are perceived severity with a p-value of 0.000 and cues to action (a cue to act) with a p-value of 0.005. Based on the research results that have been obtained, it is expected that the company can design, create or improve programs or systems regarding increasing perceived severity and cues to action for workers in the blasting and painting unit of PT. McDermott Indonesia.